1977
DOI: 10.1210/endo-101-6-1890
|View full text |Cite
|
Sign up to set email alerts
|

POTENT INHIBITORY ACTIVITY OF [D-LEU6, DES-GLY-NH21Q]LHRH ETHYLAMIDE ON LH/hCG AND PRL TESTICULAR RECEPTOR LEVELS IN THE RAT

Abstract: Injection of male rats with 40-200 ng of [D-Leu6, des-Gly-NH2(10)]LHRH ethylamide for 7 days caused a maximal 80% reduction of testicular LH/hCG receptor level with one injection per day being as efficient as 3 daily injections. A similar inhibitory effect was observed on testicular PRL receptors. Testis and seminal vesicle weight as well as plasma testosterone levels were also significantly reduced by this treatment. These data indicate that a LHRH agonist, when given at a relatively low dose, is capable of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

1979
1979
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(34 citation statements)
references
References 0 publications
3
31
0
Order By: Relevance
“…This pattern of response was typical ofthat seen in man (14) and is in marked contrast to the pattern seen in the laboratory rat, perhaps because of the prolonged halflife ofhCG in man when compared with the rat (15,16). Stimulation of the rat testis in vivo leads to a testosterone response within 15 min and a 5-to 10-fold increase by [2][3][4][5][6][7][8][9][10][11][12] h, followed by a decline to normal levels within 1-2 d depending upon the administered dose of gonadotropin (1,2). The serum 17a-hydroxyprogesterone response of the hyperstimulated primate testes was similar to the pattern of testosterone response seen in the rat.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…This pattern of response was typical ofthat seen in man (14) and is in marked contrast to the pattern seen in the laboratory rat, perhaps because of the prolonged halflife ofhCG in man when compared with the rat (15,16). Stimulation of the rat testis in vivo leads to a testosterone response within 15 min and a 5-to 10-fold increase by [2][3][4][5][6][7][8][9][10][11][12] h, followed by a decline to normal levels within 1-2 d depending upon the administered dose of gonadotropin (1,2). The serum 17a-hydroxyprogesterone response of the hyperstimulated primate testes was similar to the pattern of testosterone response seen in the rat.…”
Section: Resultsmentioning
confidence: 56%
“…Furthermore, our data on desensitization of the primate LH receptor enhances the possibility of such a mechanism having a physiological role in the control and maintenance of human gonadal function. These data further suggest that negative regulation ofovarian and testicular function by gonadotropin-releasing hormone and its analogues (3,4) should also be effective in man, an approach that offers interesting possibilities for fertility control.…”
Section: Resultsmentioning
confidence: 80%
“…A marked inhibition of pituitary and gonadal function that occurs after chronic administration of the D-Trp6 analog of luteinizing hormone-releasing hormone (LH-RH) and other LH-RH agonists (1)(2)(3)(4)(5)(6)(7)(8)(9) leads to a chemical castration and makes possible an additional approach for the treatment of sex hormone-dependent tumors (10,11). In previous studies we have shown that chronic administration of [D-Trp6]LH-RH suppressed prostate tumor growth in two different rat models (12,13).…”
mentioning
confidence: 99%
“…Desensitization of the gonads to gonadotropins is regarded as an important mechanism for the reduction in the sex hormone concentration caused by GnRH agonists (Auclair et al, 1978;Tcholakian et al, 1978;Fraser and Baird, 1987). Desensitization of the gonads is often associated with high serum gonadotropin concentrations (Bhasin & Swerdoff, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…GnRH agonists both stimulate and inhibit gonadal function depending on the dose and duration of treatment in man and laboratory animals (Auclair et al, 1978;Rivier et al, 1979;Bhasin & Swerdloff, 1986). The inhibition of gonadal function caused by chronic treatment with these potent GnRH agonists, i.e.…”
Section: Potentmentioning
confidence: 99%